In Silico Identification and Biological Evaluation of Antioxidant Food Components Endowed with Human Carbonic Anhydrase IX and XII Inhibition - Giosuè Costa; Annalisa Maruca; Roberta Rocca; Francesca Alessandra Ambrosio; Emanuela Berrino; Fabrizio Carta; Francesco Mesiti; Alessandro Salatino; Delia Lanzillotta; Francesco Trapasso; Anna Artese; Stefano Alcaro; et al. (MDPI AG, 2020)
The tumor-associated isoenzymes hCA IX and hCA XII catalyze the hydration of carbon dioxide to bicarbonate and protons. These isoforms are highly overexpressed in many types of cancer, where they contribute to the acidification of the tumor environment, promoting tumor cell invasion and metastasis. In this work, in order to identify novel dual hCA IX and XII inhibitors, virtual screening techniques and biological assays were combined. A structure-based virtual screening towards hCA IX and XII was performed using a database of approximately 26,000 natural compounds. The best shared hits were submitted to a thermodynamic analysis and three promising best hits were identified and evaluated in terms of their hCA IX and XII inhibitor activity. In vitro biological assays were in line with the theoretical studies and revealed that syringin, lithospermic acid, and (-)-dehydrodiconiferyl alcohol behave as good hCA IX and hCA XII dual inhibitors.